Operationalising resilience-based management at scale: A meta-adaptive blueprint from the Great Barrier Reef crown-of-thorns starfish control program - Samuel A. Matthews; Michael Bode; Roger Beeden; Mary C. Bonin; Cameron S. Fletcher; Brigid Kerrigan; Isobel Ryan; Jennifer Wilmes; Alice White; David H. Williamson (Biological Conservation, 2026)

Survival of dogs with myxomatous mitral valve disease administered preclinical pimobendan in comparison to pimobendan-naïve dogs from the onset of congestive heart failure - G. McAulay; M. Hills; J. Dukes-McEwan; E. Dutton; A. Jakubczak; D. Singleton; E. Bode; W. Yangwanitset; M. Hezzell (Journal of Veterinary Cardiology, 2026)

Genetic diversity and population structure analysis in Tunisian Olive collection using genotyping-by-sequencing - Sofiane Abdelhamid; Amira Araouki; Hechmi Chehab; Bode A. Olukolu; Hudson Ashrafi (Euro-Mediterranean Journal for Environmental Integration, 2026)

Effects of Nutrition Interventions on Inflammatory Biomarkers and Quality of Life in Adults with Multiple Sclerosis: A Scoping Review - C. Bode; C. Sealey Potts; A. Hashmi (Journal of the Academy of Nutrition and Dietetics, 2025)

Enhancing Nutrition Intervention Monitoring Through Computed Tomography Body Composition Assessment: A Case Study in Esophageal and Gastric Adenocarcinoma - M. Garcia Luis; C. Bury; A. Bode (Journal of the Academy of Nutrition and Dietetics, 2025)

Calibrated Ecosystem Models Cannot Predict the Consequences of Conservation Management Decisions—Clarification - Larissa Lubiana Botelho; Cailan Jeynes‐Smith; Sarah A. Vollert; Michael Bode (Ecology Letters, 2025)
Woodstock and Harris raise concerns about generalisations in our paper ‘Calibrated Ecosystem Models Cannot Predict the Consequences of Conservation Management Decisions’. They implied that our conclusions are invalidated by the exclusion of density dependent compensatory feedback and the existence of automated calibration approaches with overfitting penalties—claims that overlook the broader structural issues we identified. Here, we explore their key criticism in more detail, clarify our position and explain why we continue to stand by our findings.

P27-25 New approach for analysis of lung clearance kinetics in rats leading to a reduction of animal testing and improvement of chemical safety assessment - G. Bruer; M. Bode; K. Blümlein; O. Creutzenberg; D. Gõdecke; M. Breva; A. Garabatos; A. Burzlaff (Toxicology Letters, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Calibrated Ecosystem Models Cannot Predict the Consequences of Conservation Management Decisions - Larissa Lubiana Botelho; Cailan Jeynes‐Smith; Sarah A. Vollert; Michael Bode (Ecology Letters, 2025)
Ecosystem models are often used to predict the consequences of management interventions in applied ecology and conservation. These models are often high‐dimensional and nonlinear, yet limited data are available to calibrate or validate them. Consequently, their utility as decision‐support tools is unclear. In this paper, we calibrate ecosystem models to time series data from 110 different experimental microcosm ecosystems, each containing three to five interacting species. Then, we assess their ability to predict the consequences of management interventions. Our results show that for each time series dataset, multiple divergent parameter sets offer equivalent, good fits. However, these models have poor predictive accuracy when forecasting future dynamics or when predicting how the ecosystem will respond to management intervention. Closer inspection reveals that the models fail because calibration cannot determine the nature of the interspecific interactions. Our findings question whether ecosystem models can support applied ecological decision‐making when calibrated against real‐world datasets.

Dispersal patterns of sandfish (Holothuria scabra) larvae in Manus Province, Papua New Guinea - Peter Waldie; David A. Feary; Michael Bode; Manuai Matawai; Hugo B. Harrison; Michael L. Berumen; Chris Molai; Maunoa Karo; Richard J. Hamilton (Frontiers in Marine Science, 2024)
In many tropical nations, coastal communities seek to manage their sea cucumber fisheries by establishing locally managed marine areas on their traditional fishing grounds. These managed areas can protect spawning stocks, however the extent to which they help to replenish nearby sea cucumber fisheries is debated, as nothing is known about the scales at which sea cucumber larvae disperse. In this study, we used genetic parentage analyses and statistical modelling to provide the first empirical measure of larval dispersal patterns for a sea cucumber species. We analysed tissue samples from 765 adult and 827 juvenile sandfish ( Holothuria scabra ) collected from five traditional fishing grounds of the Titan tribe, from Manus Province, Papua New Guinea. All adults were sampled from the Pere fishing grounds (the larval source area), with juveniles sampled from the Pere, Mbunai, Tawi, Timonai and Mbuke fishing grounds. Parentage analysis identified 15 juveniles that were the offspring of parents sampled from Pere fishing grounds, with six of these juveniles located in the same fishing grounds as their parents. The best-fit larval dispersal kernel predicted that the average H. scabra larvae travelled 15 km from its spawning location, with 50% of larvae settling within 6.7 km of their parents and 95% of larvae settling within 59 km of their parents. These results suggest that the Titan tribes’ desire to protect their H. scabra spawning stocks by establishing a network of locally managed marine areas across 65 km of continuous coastline is a culturally appropriate strategy, which has merit from both an ecological and fisheries standpoint.

Seasonal upwelling influence on trophic indices of mesozooplankton in a coastal food web estimated from δ15N in amino acids - R. García-Seoane; I.G. Viana; A. Bode (Progress in Oceanography, 2023)

Pacemaker-lead-associated thrombosis in dogs: a multicenter retrospective study - C. McGrath; A. Dixon; C. Hirst; E.F. Bode; T. DeFrancesco; R. Fries; S. Gordon; D. Hogan; Y. Martinez Pereira; E. Mederska; S. Ostenkamp; K.T. Sykes; et al. (Journal of Veterinary Cardiology, 2023)

Green and sustainable solvents for biocatalytic oxidations - Roger A. Sheldon; Moira L. Bode; Nompumelelo Mathebula (Current Opinion in Green and Sustainable Chemistry, 2023)

Using MixSIAR to quantify mixed contributions of primary producers from amino acid δ15N of marine consumers - R. García-Seoane; I.G. Viana; A. Bode (Marine Environmental Research, 2023)

Modeling total predation to avoid perverse outcomes from cat control in a data‐poor island ecosystem - Michaela Plein; Katherine R. O'Brien; Matthew H. Holden; Matthew P. Adams; Christopher M. Baker; Nigel G. Bean; Scott A. Sisson; Michael Bode; Kerrie L. Mengersen; Eve McDonald‐Madden (Conservation Biology, 2022)
Data‐hungry, complex ecosystem models are often used to predict the consequences of threatened species management, including perverse outcomes. Unfortunately, this approach is impractical in the many systems that have insufficient data to parameterize ecosystem interactions or reliably calibrate or validate such models. We devised a different approach composed of a minimum realistic model that guides decisions in data‐ and resource‐scarce systems. We applied our approach to a case study in an invaded ecosystem from Christmas Island, Australia, where there are concerns that cat ( Felis catus ) eradication to protect native species, including the red‐tailed tropicbird ( Phaethon rubricauda ), could release mesopredation by invasive rats ( Rattus rattus ). We used biophysical constraints (metabolic demand) and observable parameters (e.g., prey preferences) to identify the combined cat and rat abundances that could threaten the tropicbird population. The population of tropicbirds was not sustained when predated by 1607 rats (95% credible interval [CI]: 103–5910) in the absence of cats and 21 cats (95% CI: 2–82) in the absence of rats. For every cat removed from the island, the bird's net population growth rate improved, provided rats did not increase by more than 77 individuals (95% CI: 30–174). Thus, in this context, 1 cat is equivalent to 30–174 rats. Our methods are especially useful for on‐the‐ground predator control in the absence of knowledge of predator–predator interactions to determine whether current abundance of predators threatened the prey population of interest; managing only 1 predator species was sufficient to protect the prey species given potential release of another predator; and control of multiple predator species was needed to meet the conservation goal. With our approach limited information can be used for maximum value in data‐poor systems because it shifts the focus from predicting future trajectories to identifying conditions that impede conservation.

Mapping and identification of QTL in 5601T × U99-310255 RIL population using SNP genotyping: soybean seed quality traits - Mia Cunicelli; Bode A. Olukolu; Carl Sams; Liesel Schneider; Dennis West; Vincent Pantalone (Molecular Biology Reports, 2022)

Synthetische Zipper für die Biosynthese neuer Naturstoffderivate - Nadya Abbood; Kenan A. J. Bozhüyük; Helge B. Bode (BIOspektrum, 2022)
A rich source of new therapeutics are natural products derived from modular non-ribosomal peptide synthetases (e. g. penicillins, daptomycin). Yet, efficient bioengineering of these often gigantic megaenzymes to generate natural product analogs is a major challenge. Using synthetic zippers, we have established a co-expression strategy that not only simplifies bioengineering, but rapidly increases the biocombinatorial potential and throughput of reprogrammed NRPS.

Pro- and anti-inflammatory macrophages express a sub-type specific purinergic receptor profile - J. Merz; A. Nettesheim; S. von Garlen; P. Albrecht; B. S. Saller; J. Engelmann; L. Hertle; I. Schäfer; D. Dimanski; S. König; L. Karnbrock; K. Bulatova; et al. (Purinergic Signalling, 2021)
Extracellular nucleotides act as danger signals that orchestrate inflammation by purinergic receptor activation. The expression pattern of different purinergic receptors may correlate with a pro- or anti-inflammatory phenotype. Macrophages function as pro-inflammatory M1 macrophages (M1) or anti-inflammatory M2 macrophages (M2). The present study found that murine bone marrow-derived macrophages express a unique purinergic receptor profile during in vitro polarization. As assessed by real-time polymerase chain reaction (PCR), Gαs-coupled P1 receptors A2A and A2B are upregulated in M1 and M2 compared to M0, but A2A 15 times higher in M1. The ionotropic P2 receptor P2X 5 is selectively upregulated in M1- and M2-polarized macrophages. P2X 7 is temporarily expressed in M1 macrophages. Metabotropic P2Y receptors showed a distinct expression profile in M1 and M2-polarized macrophages: Gαq coupled P2Y 1 and P2Y 6 are exclusively upregulated in M2, whereas Gαi P2Y 13 and P2Y 14 are overexpressed in M1. This consequently leads to functional differences between M1 and M2 in response to adenosine di-phosphate stimulation (ADP): In contrast to M1, M2 showed increased cytoplasmatic calcium after ADP stimulation. In the present study we show that bone marrow-derived macrophages express a unique repertoire of purinergic receptors. We show for the first time that the repertoire of purinergic receptors is highly flexible and quickly adapts upon pro- and anti-inflammatory macrophage differentiation with functional consequences to nucleotide stimulation.

Discovery of a major QTL for root-knot nematode (Meloidogyne incognita) resistance in cultivated sweetpotato (Ipomoea batatas) - Bonny Michael Oloka; Guilherme da Silva Pereira; Victor A. Amankwaah; Marcelo Mollinari; Kenneth V. Pecota; Benard Yada; Bode A. Olukolu; Zhao-Bang Zeng; G. Craig Yencho (Theoretical and Applied Genetics, 2021)
Key message Utilizing a high-density integrated genetic linkage map of hexaploid sweetpotato, we discovered a major dominant QTL for root-knot nematode (RKN) resistance and modeled its effects. This discovery is useful for development of a modern sweetpotato breeding program that utilizes marker-assisted selection and genomic selection approaches for faster genetic gain of RKN resistance. Abstract The root-knot nematode [Meloidogyne incognita (Kofoid & White) Chitwood] (RKN) causes significant storage root quality reduction and yields losses in cultivated sweetpotato [Ipomoea batatas (L.) Lam.]. In this study, resistance to RKN was examined in a mapping population consisting of 244 progenies derived from a cross (TB) between ‘Tanzania,’ a predominant African landrace cultivar with resistance to RKN, and ‘Beauregard,’ an RKN susceptible major cultivar in the USA. We performed quantitative trait loci (QTL) analysis using a random-effect QTL mapping model on the TB genetic map. An RKN bioassay incorporating potted cuttings of each genotype was conducted in the greenhouse and replicated five times over a period of 10 weeks. For each replication, each genotype was inoculated with ca. 20,000 RKN eggs, and root-knot galls were counted ~62 days after inoculation. Resistance to RKN in the progeny was highly skewed toward the resistant parent, exhibiting medium to high levels of resistance. We identified one major QTL on linkage group 7, dominant in nature, which explained 58.3% of the phenotypic variation in RKN counts. This work represents a significant step forward in our understanding of the genetic architecture of RKN resistance and sets the stage for future utilization of genomics-assisted breeding in sweetpotato breeding programs.

Case–Case Comparison of Candida auris Versus Other Candida Species Bloodstream Infections: Results of an Outbreak Investigation in Colombia - Diego H. Caceres; Sandra M. Rivera; Paige A. Armstrong; Patricia Escandon; Nancy A. Chow; Maria Victoria Ovalle; Jorge Díaz; Gordana Derado; Soraya Salcedo; Indira Berrio; Andres Espinosa-Bode; Carmen Varón; et al. (Mycopathologia, 2020)

Quantitative trait loci and differential gene expression analyses reveal the genetic basis for negatively associated β-carotene and starch content in hexaploid sweetpotato [Ipomoea batatas (L.) Lam.] - Dorcus C. Gemenet; Guilherme da Silva Pereira; Bert De Boeck; Joshua C. Wood; Marcelo Mollinari; Bode A. Olukolu; Federico Diaz; Veronica Mosquera; Reuben T. Ssali; Maria David; Mercy N. Kitavi; Gabriela Burgos; et al. (Theoretical and Applied Genetics, 2020)
Key message β-Carotene content in sweetpotato is associated with the Orange and phytoene synthase genes; due to physical linkage of phytoene synthase with sucrose synthase , β-carotene and starch content are negatively correlated. Abstract In populations depending on sweetpotato for food security, starch is an important source of calories, while β-carotene is an important source of provitamin A. The negative association between the two traits contributes to the low nutritional quality of sweetpotato consumed, especially in sub-Saharan Africa. Using a biparental mapping population of 315 F 1 progeny generated from a cross between an orange-fleshed and a non-orange-fleshed sweetpotato variety, we identified two major quantitative trait loci (QTL) on linkage group (LG) three (LG3) and twelve (LG12) affecting starch, β-carotene, and their correlated traits, dry matter and flesh color. Analysis of parental haplotypes indicated that these two regions acted pleiotropically to reduce starch content and increase β-carotene in genotypes carrying the orange-fleshed parental haplotype at the LG3 locus. Phytoene synthase and sucrose synthase, the rate-limiting and linked genes located within the QTL on LG3 involved in the carotenoid and starch biosynthesis, respectively, were differentially expressed in Beauregard versus Tanzania storage roots. The Orange gene, the molecular switch for chromoplast biogenesis, located within the QTL on LG12 while not differentially expressed was expressed in developing roots of the parental genotypes. We conclude that these two QTL regions act together in a cis and trans manner to inhibit starch biosynthesis in amyloplasts and enhance chromoplast biogenesis, carotenoid biosynthesis, and accumulation in orange-fleshed sweetpotato. Understanding the genetic basis of this negative association between starch and β-carotene will inform future sweetpotato breeding strategies targeting sweetpotato for food and nutritional security.

Cyclo(tetrahydroxybutyrate) production is sufficient to distinguish between Xenorhabdus and Photorhabdus isolates in Thailand - Nicholas J. Tobias; César Parra‐Rojas; Yan‐Ni Shi; Yi‐Ming Shi; Svenja Simonyi; Aunchalee Thanwisai; Apichat Vitta; Narisara Chantratita; Esteban A. Hernandez‐Vargas; Helge B. Bode (Environmental Microbiology, 2019)
Summary Bacteria of the genera Photorhabdus and Xenorhabdus produce a plethora of natural products to support their similar symbiotic life cycles. For many of these compounds, the specific bioactivities are unknown. One common challenge in natural product research when trying to prioritize research efforts is the rediscovery of identical (or highly similar) compounds from different strains. Linking genome sequence to metabolite production can help in overcoming this problem. However, sequences are typically not available for entire collections of organisms. Here, we perform a comprehensive metabolic screening using HPLC‐MS data associated with a 114‐strain collection (58 Photorhabdus and 56 Xenorhabdus ) across Thailand and explore the metabolic variation among the strains, matched with several abiotic factors. We utilize machine learning in order to rank the importance of individual metabolites in determining all given metadata. With this approach, we were able to prioritize metabolites in the context of natural product investigations, leading to the identification of previously unknown compounds. The top three highest ranking features were associated with Xenorhabdus and attributed to the same chemical entity, cyclo(tetrahydroxybutyrate). This work also addresses the need for prioritization in high‐throughput metabolomic studies and demonstrates the viability of such an approach in future research.

Trace element measurement for assessment of dog food safety - Elisabete A. De Nadai Fernandes; Camila Elias; Márcio Arruda Bacchi; Peter Bode (Environmental Science and Pollution Research, 2018)

Minimizing species extinctions through strategic planning for conservation fencing - Jeremy L. Ringma; Brendan Wintle; Richard A. Fuller; Diana Fisher; Michael Bode (Conservation Biology, 2017)
Conservation fences are an increasingly common management action, particularly for species threatened by invasive predators. However, unlike many conservation actions, fence networks are expanding in an unsystematic manner, generally as a reaction to local funding opportunities or threats. We conducted a gap analysis of Australia's large predator‐exclusion fence network by examining translocation of Australian mammals relative to their extinction risk. To address gaps identified in species representation, we devised a systematic prioritization method for expanding the conservation fence network that explicitly incorporated population viability analysis and minimized expected species’ extinctions. The approach was applied to New South Wales, Australia, where the state government intends to expand the existing conservation fence network. Existing protection of species in fenced areas was highly uneven; 67% of predator‐sensitive species were unrepresented in the fence network. Our systematic prioritization yielded substantial efficiencies in that it reduced expected number of species extinctions up to 17 times more effectively than ad hoc approaches. The outcome illustrates the importance of governance in coordinating management action when multiple projects have similar objectives and rely on systematic methods rather than expanding networks opportunistically.

Reef-fish larval dispersal patterns validate no-take marine reserve network connectivity that links human communities - Rene A. Abesamis; Pablo Saenz-Agudelo; Michael L. Berumen; Michael Bode; Claro Renato L. Jadloc; Leilani A. Solera; Cesar L. Villanoy; Lawrence Patrick C. Bernardo; Angel C. Alcala; Garry R. Russ (Coral Reefs, 2017)

Hyperstability masks declines in bumphead parrotfish (Bolbometopon muricatum) populations - Richard J. Hamilton; Glenn R. Almany; Don Stevens; Michael Bode; John Pita; Nate A. Peterson; J. Howard Choat (Coral Reefs, 2016)

A systematic review and meta-analysis on Staphylococcus aureus carriage in psoriasis, acne and rosacea - J. E. E. Totté; W. T. van der Feltz; L. G. M. Bode; A. van Belkum; E. J. van Zuuren; S. G. M. A. Pasmans (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Global transcriptome analyses provide evidence that chloroplast redox state contributes to intracellular as well as long-distance signalling in response to stress and acclimation in Arabidopsis - Rainer Bode; Alexander G. Ivanov; Norman P. A. Hüner (Photosynthesis Research, 2016)

Resolving future fire management conflicts using multicriteria decision making - Don A. Driscoll; Michael Bode; Ross A. Bradstock; David A. Keith; Trent D. Penman; Owen F. Price (Conservation Biology, 2016)
Management strategies to reduce the risks to human life and property from wildfire commonly involve burning native vegetation. However, planned burning can conflict with other societal objectives such as human health and biodiversity conservation. These conflicts are likely to intensify as fire regimes change under future climates and as growing human populations encroach farther into fire‐prone ecosystems. Decisions about managing fire risks are therefore complex and warrant more sophisticated approaches than are typically used. We applied a multicriteria decision making approach (MCDA) with the potential to improve fire management outcomes to the case of a highly populated, biodiverse, and flammable wildland–urban interface. We considered the effects of 22 planned burning options on 8 objectives: house protection, maximizing water quality, minimizing carbon emissions and impacts on human health, and minimizing declines of 5 distinct species types. The MCDA identified a small number of management options (burning forest adjacent to houses) that performed well for most objectives, but not for one species type (arboreal mammal) or for water quality. Although MCDA made the conflict between objectives explicit, resolution of the problem depended on the weighting assigned to each objective. Additive weighting of criteria traded off the arboreal mammal and water quality objectives for other objectives. Multiplicative weighting identified scenarios that avoided poor outcomes for any objective, which is important for avoiding potentially irreversible biodiversity losses. To distinguish reliably among management options, future work should focus on reducing uncertainty in outcomes across a range of objectives. Considering management actions that have more predictable outcomes than landscape fuel management will be important. We found that, where data were adequate, an MCDA can support decision making in the complex and often conflicted area of fire management.

The Effect of Excipients on the Permeability of BCS Class III Compounds and Implications for Biowaivers - Alan Parr; Ismael J. Hidalgo; Chris Bode; William Brown; Mehran Yazdanian; Mario A. Gonzalez; Kazuko Sagawa; Kevin Miller; Wenlei Jiang; Erika S. Stippler (Pharmaceutical Research, 2016)

The genetic basis of flecking and its relationship to disease resistance in the IBM maize mapping population - Vijay Vontimitta; Bode A. Olukolu; Bryan W. Penning; Gurmukh Johal; P. J. Balint-Kurti (Theoretical and Applied Genetics, 2015)

Minimizing the Cost of Keeping Options Open for Conservation in a Changing Climate - MORENA MILLS; SAM NICOL; JESSIE A. WELLS; JOSÉ J. LAHOZ‐MONFORT; BRENDAN WINTLE; MICHAEL BODE; MARTIN WARDROP; TERRY WALSHE; WILLIAM J. M. PROBERT; MICHAEL C. RUNGE; HUGH P. POSSINGHAM; EVE MCDONALD MADDEN (Conservation Biology, 2014)
Policy documents advocate that managers should keep their options open while planning to protect coastal ecosystems from climate‐change impacts. However, the actual costs and benefits of maintaining flexibility remain largely unexplored, and alternative approaches for decision making under uncertainty may lead to better joint outcomes for conservation and other societal goals. For example, keeping options open for coastal ecosystems incurs opportunity costs for developers. We devised a decision framework that integrates these costs and benefits with probabilistic forecasts for the extent of sea‐level rise to find a balance between coastal ecosystem protection and moderate coastal development. Here, we suggest that instead of keeping their options open managers should incorporate uncertain sea‐level rise predictions into a decision‐making framework that evaluates the benefits and costs of conservation and development. In our example, based on plausible scenarios for sea‐level rise and assuming a risk‐neutral decision maker, we found that substantial development could be accommodated with negligible loss of environmental assets. Characterization of the Pareto efficiency of conservation and development outcomes provides valuable insight into the intensity of trade‐offs between development and conservation. However, additional work is required to improve understanding of the consequences of alternative spatial plans and the value judgments and risk preferences of decision makers and stakeholders. Minimizando el Costo de Mantener Opciones Abiertas para la Conservación en un Clima Cambiante

Assisting vascular access surgery planning for hemodialysis by using MR, image segmentation techniques, and computer simulations - M. A. G. Merkx; A. S. Bode; W. Huberts; J. Oliván Bescós; J. H. M. Tordoir; M. Breeuwer; F. N. van de Vosse; E. M. H. Bosboom (Medical & Biological Engineering & Computing, 2013)

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

A physical map of the Chinese chestnut (Castanea mollissima) genome and its integration with the genetic map - Guang-Chen Fang; Barbara P. Blackmon; Margaret E. Staton; C. Dana Nelson; Thomas L. Kubisiak; Bode A. Olukolu; David Henry; Tatyana Zhebentyayeva; Christopher A. Saski; Chun-Huai Cheng; Megan Monsanto; Stephen Ficklin; et al. (Tree Genetics & Genomes, 2013)

Leading from the front? Social networks in navigating groups - Nikolai W. F. Bode; Daniel W. Franks; A. Jamie Wood (Behavioral Ecology and Sociobiology, 2012)

Genetic diversity in Bambara groundnut (Vigna subterranea (L.) Verdc.) as revealed by phenotypic descriptors and DArT marker analysis - Bode A. Olukolu; Sean Mayes; Florian Stadler; N. Quat Ng; Iyiwole Fawole; Dumet Dominique; Sayed N. Azam-Ali; Albert G. Abbott; Chittaranjan Kole (Genetic Resources and Crop Evolution, 2012)

Pathologic progression of mammary carcinomas in a C3(1)/SV40 T/t-antigen transgenic rat model of human triple-negative and Her2-positive breast cancer - M. J. Hoenerhoff; M. A. Shibata; A. Bode; J. E. Green (Transgenic Research, 2011)

Conservation Planning with Multiple Organizations and Objectives - MICHAEL BODE; WILL PROBERT; WILL R. TURNER; KERRIE A. WILSON; OSCAR VENTER (Conservation Biology, 2011)
There has been a dramatic increase in the number of conservation organizations worldwide. It is now common for multiple organizations to operate in the same landscape in pursuit of different conservation goals. New objectives, such as maintenance of ecosystem services, will attract additional funding and new organizations to conservation. Systematic conservation planning helps in the design of spatially explicit management actions that optimally conserve multiple landscape features (e.g., species, ecosystems, or ecosystem services). But the methods used in its application implicitly assume that a single actor implements the optimal plan. We investigated how organizational behavior and conservation outcomes are affected by the presence of autonomous implementing organizations with different objectives. We used simulation models and game theory to explore how alternative behaviors (e.g., organizations acting independently or explicitly cooperating) affected an organization's ability to protect their feature of interest, and investigated how the distribution of features in the landscape influenced organizations’ attitudes toward cooperation. Features with highly correlated spatial distributions, although typically considered an opportunity for mutually beneficial conservation planning, can lead to organizational interactions that result in lower levels of protection. These detrimental outcomes can be avoided by organizations that cooperate when acquiring land. Nevertheless, for cooperative purchases to benefit both organizations’ objectives, each must forgo the protection of land parcels that they would consider to be of high conservation value. Transaction costs incurred during cooperation and the sources of conservation funding could facilitate or hinder cooperative behavior.

Social networks and models for collective motion in animals - Nikolai W. F. Bode; A. Jamie Wood; Daniel W. Franks (Behavioral Ecology and Sociobiology, 2011)

Safeguarding Biodiversity and Ecosystem Services in the Little Karoo, South Africa - BENIS N. EGOH; BELINDA REYERS; JOSIE CARWARDINE; MICHAEL BODE; PATRICK J. O'FARRELL; KERRIE A. WILSON; HUGH P. POSSINGHAM; MATHIEU ROUGET; WILLEM De LANGE; DAVID M. RICHARDSON; RICHARD M. COWLING (Conservation Biology, 2010)
Global declines in biodiversity and the widespread degradation of ecosystem services have led to urgent calls to safeguard both. Responses to this urgency include calls to integrate the needs of ecosystem services and biodiversity into the design of conservation interventions. The benefits of such integration are purported to include improvements in the justification and resources available for these interventions. Nevertheless, additional costs and potential trade‐offs remain poorly understood in the design of interventions that seek to conserve biodiversity and ecosystem services. We sought to investigate the synergies and trade‐offs in safeguarding ecosystem services and biodiversity in South Africa's Little Karoo. We used data on three ecosystem services—carbon storage, water recharge, and fodder provision—and data on biodiversity to examine several conservation planning scenarios. First, we investigated the amount of each ecosystem service captured incidentally by a conservation plan to meet targets for biodiversity only while minimizing opportunity costs. We then examined the costs of adding targets for ecosystem services into this conservation plan. Finally, we explored trade‐offs between biodiversity and ecosystem service targets at a fixed cost. At least 30% of each ecosystem service was captured incidentally when all of biodiversity targets were met. By including data on ecosystem services, we increased the amount of services captured by at least 20% for all three services without additional costs. When biodiversity targets were reduced by 8%, an extra 40% of fodder provision and water recharge were obtained and 58% of carbon could be captured for the same cost. The opportunity cost (in terms of forgone production) of safeguarding 100% of the biodiversity targets was about US$500 million. Our results showed that with a small decrease in biodiversity target achievement, substantial gains for the conservation of ecosystem services can be achieved within our biodiversity priority areas for no extra cost.

Oral Cancer Preventive Practices of South Carolina Dentists and Physicians - Susan G. Reed; Kathleen B. Cartmell; Nadia G. Duffy; Amy E. Wahlquist; Debajyoti Sinha; Amanda Hollinger; Ashley Bode; Anthony J. Alberg; Terry A. Day (Journal of Cancer Education, 2010)

Heterogeneity of the humoral immune response following Staphylococcus aureus bacteremia - N. J. Verkaik; H. A. Boelens; C. P. de Vogel; M. Tavakol; L. G. M. Bode; H. A. Verbrugh; A. van Belkum; W. J. B. van Wamel (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Klinische Wirksamkeitsprüfung von Tierarzneimitteln – ein kurzer Überblick - A. Golombiewski; K. Bode (Journal of Consumer Protection and Food Safety, 2008)

Incorporating the Effects of Socioeconomic Uncertainty into Priority Setting for Conservation Investment - MARISSA F. McBRIDE; KERRIE A. WILSON; MICHAEL BODE; HUGH P. POSSINGHAM (Conservation Biology, 2007)
Uncertainty in the implementation and outcomes of conservation actions that is not accounted for leaves conservation plans vulnerable to potential changes in future conditions. We used a decision‐theoretic approach to investigate the effects of two types of investment uncertainty on the optimal allocation of global conservation resources for land acquisition in the Mediterranean Basin. We considered uncertainty about (1) whether investment will continue and (2) whether the acquired biodiversity assets are secure, which we termed transaction uncertainty and performance uncertainty, respectively. We also developed and tested the robustness of different rules of thumb for guiding the allocation of conservation resources when these sources of uncertainty exist. In the presence of uncertainty in future investment ability (transaction uncertainty), the optimal strategy was opportunistic, meaning the investment priority should be to act where uncertainty is highest while investment remains possible. When there was a probability that investments would fail (performance uncertainty), the optimal solution became a complex trade‐off between the immediate biodiversity benefits of acting in a region and the perceived longevity of the investment. In general, regions were prioritized for investment when they had the greatest performance certainty, even if an alternative region was highly threatened or had higher biodiversity value. The improved performance of rules of thumb when accounting for uncertainty highlights the importance of explicitly incorporating sources of investment uncertainty and evaluating potential conservation investments in the context of their likely long‐term success.

Piperacillin-tazobactam in pediatric cancer patients younger than 25 months: a retrospective multicenter survey - A. Simon; T. Lehrnbecher; U. Bode; A. H. Groll; L. Tramsen; R. Wieland; E. Molitor; G. Fleischhack; H. J. Laws (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Immunogold-labeled S-phase neoblasts, total neoblast number, their distribution, and evidence for arrested neoblasts in Macrostomum lignano (Platyhelminthes, Rhabditophora) - A. Bode; W. Salvenmoser; K. Nimeth; M. Mahlknecht; Z. Adamski; R. M. Rieger; R. Peter; P. Ladurner (Cell and Tissue Research, 2006)

Evaluation of Cancer-Preventive Activity and Structure–Activity Relationships of 3-Demethylubiquinone Q2, Isolated from the Ascidian Aplidium glabrum, and its Synthetic Analogs - Sergey N. Fedorov; Oleg S. Radchenko; Larisa K. Shubina; Nadezhda N. Balaneva; Ann M. Bode; Valentin A. Stonik; Zigang Dong (Pharmaceutical Research, 2006)

Marine Alkaloid Polycarpine and Its Synthetic Derivative Dimethylpolycarpine Induce Apoptosis in JB6 Cells Through p53- and Caspase 3-Dependent Pathways - Sergey N. Fedorov; Ann M. Bode; Valentin A. Stonik; Irina A. Gorshkova; Patricia C. Schmid; Oleg S. Radchenko; Evgueni V. Berdyshev; Zigang Dong (Pharmaceutical Research, 2004)

ICAM-1 supports adhesion of human small-cell lung carcinoma to endothelial cells - Angela H. Finzel; Armin J. Reininger; Patrick A. Bode; Laurenz J. Wurzinger (Clinical & Experimental Metastasis, 2004)

From DNA structure to gene expression: mediators of nuclear compartmentalization and dynamics - J. Bode; S. Goetze; H. Heng; S. A. Krawetz; C. Benham (Chromosome Research, 2003)

Effects of ENU dosage on mouse strains - Monica J. Justice; Don A. Carpenter; Jack Favor; Angelika Neuhauser-Klaus; Martin Hrabé de Angelis; Dian Soewarto; Amy Moser; Sabine Cordes; Darla Miller; Verne Chapman; John S. Weber; Eugene M. Rinchik; et al. (Mammalian Genome, 2000)

Nitrate storage by phytoplankton in a coastal upwelling environment - A. Bode; J. A. Botas; E. Fernández (Marine Biology, 1997)

Long-wavelength global gravity field models: GRIM4-S4, GRIM4-C4 - P. Schwintzer; C. Reigber; A. Bode; Z. Kang; S. Y. Zhu; F.-H. Massmann; J. C. Raimondo; R. Biancale; G. Balmino; J. M. Lemoine; B. Moynot; J. C. Marty; et al. (Journal of Geodesy, 1997)